Réponses

2014-03-03T19:54:03+01:00
Bonsoir


1. x- 2 (3x - 8) = 0
x - 6x + 16 = 0
-5x + 16 = 0
-5x = -16
x = -16/(-5)
x = 16/5
x = 3,2

2. (x - 2) + (3x - 8) = 0
x - 2 + 3x - 8 = 0
4x - 10 = 0
4x = 10
x = 10/4
x = 5/2

3. (x - 2)(3x - 8) = 0
x - 2 = 0  ou  3x - 8 = 0
x = 2   ou   3x = 8
x = 2   ou  x = 8/3

4. (x - 2)(3x - 8) = 16 ( on pourra commencer par développer le premier membre)
3x² - 8x - 6x + 16 = 16
3x² - 8x - 6x + 16 - 16 = 0
3x² - 14x = 0
x(3x - 14) = 0
x = 0   ou   3x - 14 = 0
x = 0   ou   3x = 14
x = 0   ou  x = 14/3

5. (x - 2)(3x - 8) = -14x 
3x² - 8x - 6x + 16 = -14x
3x² - 8x - 6x + 16 + 14x = 0
3x² + 16 = 0
3x² = -16
Equation impossible car 3x² ne peut pas être négatif.